Vehicle remote control using spread spectrum technology - Chiu, Yan Chun. (2008)
Many cars have been installed with remote control systems for drivers' convenience and in near future vehicle remote controls will become standards for cars. However, vehicle remote control systems are facing two types of security attacks, code scanning attacks and code grabbing attacks. Thieves can gain illegal accesses to vehicles with code scanners or code grabbers. Although anti-code scanning techniques and anti-grabbing techniques have been applied to remedy these problems, the techniques cannot eliminate these problems completely.